Eruptive acral syringomas: A case report and review of literature - María Gabriela Rodríguez Herrera; Stephen M. Smith; Cheryl F. Rosen (SAGE Open Medical Case Reports)
We present a case of a 43-year-old woman with Vogt–Koyanagi–Harada syndrome, on adalimumab, methotrexate, and risedronate, who developed pruritic, skin-colored papules on the dorsal hands. A biopsy revealed features consistent with syringomas. Syringomas are benign eccrine duct tumors that typically appear as small, shiny papules, most often in the periorbital area but can also present in acral regions. Only 14 cases of exclusive acral syringomas have been reported. Eruptive variants may resemble conditions such as lichen nitidus or warts, making dermoscopy and histopathology crucial for diagnosis. Dermoscopically, syringomas may show fine reticulate brown lines and homogenous pigmentation. Histologically, they show small ductal structures and epithelial cords in the dermis. Their exact pathogenesis remains unclear, possibly involving hormonal or inflammatory triggers. Treatment is challenging due to their dermal depth and recurrence risk, with lasers and retinoids among the options. This case highlights the diagnostic complexity of acral eruptive syringomas.